2012
DOI: 10.1016/j.jml.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The internal structure of chaos: Letter category determines visual word perceptual units

Abstract: a b s t r a c tThe processes and the cues determining the orthographic structure of polysyllabic words remain far from clear. In the present study, we investigated the role of letter category (consonant vs. vowels) in the perceptual organization of letter strings. In the syllabic counting task, participants were presented with written words matched for the number of spoken syllables and comprising either one vowel cluster less than the number of syllables (hiatus words, e.g., pharaon) or the same number of vow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
58
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 79 publications
16
58
4
1
Order By: Relevance
“…This replicates the findings reported by Chetail and Content (2012) according to which the CV pattern constrains the orthographic structure of letter strings. More importantly, CV pattern and morphemic structure 10 underestimation occurred both in prefixed (e.g., réunion) and non-prefixed (e.g., création)…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This replicates the findings reported by Chetail and Content (2012) according to which the CV pattern constrains the orthographic structure of letter strings. More importantly, CV pattern and morphemic structure 10 underestimation occurred both in prefixed (e.g., réunion) and non-prefixed (e.g., création)…”
Section: Discussionsupporting
confidence: 91%
“…Inhibitory effects of syllabic neighbourhood have also been confirmed in masked priming experiments (e.g., Carreiras & Perea, 2002;Dominguez, de Vega, & Cuetos, 1997; in Spanish; Mathey, Doignon-Camus, & Chetail, 2013, in French). For example, Mathey et al (2013) showed that a French word like rocher (/ʀɔ.ʃe/) which has a first syllable of low frequency was recognized more slowly when it was preceded by a pseudoword prime sharing the first syllable (e.g., robane, /ʀɔban/) rather than the first letters (e.g., roisie, /ʀwasi/).The proposition that polysyllabic words are parsed into letter clusters corresponding to phonological syllables contrasts with the recent work of Chetail and Content (2012, CV pattern and morphemic structure 4 2014 Chetail, Scaltritti, & Content, in press, in Italian) suggesting that the segmentation of words into small units is primarily driven by orthographic cues. According to this hypothesis, the organization of consonant and vowel letters within words (i.e., the CV pattern) constrains the perceptual structure of letter strings, with each vowel or vowel cluster underlying one orthographic unit.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Such representations may develop during learning to read via exposure to frequently cooccurring letter combinations, as frequent orthographic syllables naturally tend to correspond to frequent orthographic clusters (Adams, 1981;Seidenberg, 1987;see Conrad et al, 2010) and orthographic chunking of letter strings into orthographic syllablelike units may be driven by the distinction between consonant and vowel letters (Chetail & Content, 2012; see also Kandel, Hé rault, Grosjacques, Lambert, & Fayol, 2009). …”
Section: Leader Strength and Competitionmentioning
confidence: 99%